4(a+2)-9=11

Simple and best practice solution for 4(a+2)-9=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(a+2)-9=11 equation:


Simplifying
4(a + 2) + -9 = 11

Reorder the terms:
4(2 + a) + -9 = 11
(2 * 4 + a * 4) + -9 = 11
(8 + 4a) + -9 = 11

Reorder the terms:
8 + -9 + 4a = 11

Combine like terms: 8 + -9 = -1
-1 + 4a = 11

Solving
-1 + 4a = 11

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 4a = 11 + 1

Combine like terms: -1 + 1 = 0
0 + 4a = 11 + 1
4a = 11 + 1

Combine like terms: 11 + 1 = 12
4a = 12

Divide each side by '4'.
a = 3

Simplifying
a = 3

See similar equations:

| 3m-2=8 | | sqrt(3x)+1=x+1 | | t^4+2lt^2+20=0 | | -4(y+3)-2y=24 | | 2x^2+170=0 | | -9(x+3)+4x=-2 | | 11x^4+21x^3-35x^2-63x+6=0 | | 8(6n+10)+6n= | | 6(x+2)-4x+6=36 | | 5x^2-135x=0 | | -6-6k-12=18 | | 4(a+3)-2(a+6)=20 | | X^2+5x=1500 | | -8(6k-8)=-272 | | 5x^4-6x=109 | | 3(y-1)+2(y+3)=13 | | 8g+4h=68 | | x^4-2x^3+x^2-12x=0 | | 8+9(9+8w)= | | 7x^2-245x=0 | | 3x+(11-x)=11 | | x-lnx(2x)=0 | | 17=13+4 | | 3x+5+4x=19 | | 6(x+2)-4x=30 | | 4+13=-17 | | 6(4x-12)=8x+9 | | 13+4=-17 | | x^3-7x^2-6x-1=0 | | 4y+2(y-2)=8 | | 2x+(1-x)=4 | | 2y+6(y+3)=32 |

Equations solver categories